Partners and Ex-Partners in Dreams: A Diary Study - Michael Schredl; Lara C. Wood (Clocks & Sleep, 2021)
Romantic relationships are an important part of human life and thus, according to the continuity hypothesis of dreaming, one’s romantic partner should show up in dreams quite frequently. The present study is based on 1612 dream reports provided by 425 students. The findings confirmed the hypothesis that partner dreams are more frequent than ex-partner dreams and, thus, support the continuity hypothesis of dreaming. Moreover, interactions with ex-partners within the dream were more often negatively toned compared to dreamed interactions with the partner. Unexpectedly, we also found more positive emotions and friendliness in ex-partner dreams compared to partner dreams, indicating that partner dreams are more mundane. To conclude, dreams reflect important aspects of romantic partnerships and their break-ups and, thus, can be very helpful in psychotherapy.